Defining the Signature of VISTA on Myeloid Cell Chemokine Responsiveness - Broughton, Thomas W. K.; ElTanbouly, Mohamed A.; Schaafsma, Evelien; Deng, Jie; Sarde, Aurélien; Croteau, Walburga; Li, Jiannan; Nowak, Elizabeth C.; Mabaera, Rodwell; Smits, Nicole C.; Kuta, Anna; Noelle, Randolph J.; et al. (Frontiers in Immunology, 2019)
The role of negative checkpoint regulators (NCRs) in human health and disease cannot be overstated. V-domain Ig-containing Suppressor of T-cell Activation (VISTA) is an Ig superfamily protein predominantly expressed within the hematopoietic compartment and has been studied for its role in the negative regulation of T cell responses. The findings presented in this study show that, unlike all other NCRs, VISTA deficiency dramatically impacts on macrophage cytokine and chemokine production, as well as the chemotactic response of VISTA-deficient macrophages. A select group of inflammatory chemokines, including CCL2, CCL3, CCL4 and CCL5, was strikingly elevated in culture supernatants from VISTA KO macrophages. VISTA deficiency also altered chemokine receptor recycling and profoundly disrupted myeloid chemotaxis. The impact of VISTA deficiency on chemotaxis in vivo was apparent with the reduced ability of both KO macrophages and MDSCs to migrate to the tumor microenvironment. This is the first demonstration of an NCR impacting on myeloid mediator production and chemotaxis and will guide the use of anti-VISTA therapeutics to manipulate the chemotaxis of inflammatory macrophages or immunosuppressive MDSCs in inflammatory diseases and cancer.